Multiple Cavitating Pulmonary Nodules Secondary To Hodgkin’s Lymphoma - Abdul Azih MN; Rahman AA; Hin HS; Chunn KY; Kori AN (Kulliyyah of Medicine, International Islamic University Malaysia, 2024)
Non-Indexed Publication